Teaching English to Young Learners: Things That The Teachers Should Consider - Arisandi Setiyawan (Wacana Didaktika, 2016)
Teaching English to young learners is challenging to the English teachers because young learners have difference point of view and character. Even though it looks so easy to teach English to young learners, the teachers should not underestimate some aspect before teaching young learners, therefore this article discusses about three aspects that should be considered by the teachers when they teach English to young learners, those are; the strategy when they teach, the characteristics of young learners and the classroom management.